Characterization of clones of west indian cherry (Malpighia glabra L.) by means of isoenzymatic peroxidase-esterase systems - Freitas, Nara Suzy Aguiar de; Burity, Hélio Almeida; Bezerra, João Emmanoel Fernandes; Silva, Márcia Vanusa da (Pesquisa Agropecuaria Brasileira, 1995)
Studies on genetic improvement of fruit trees has been utilizing genetics-biochemistry in the characterization of materials propagated vegetatively. lsoenzymatic analysis provides an adequate evaluation in recognizing accesses with the same genotype and, as far as possible, genetic variations which occur in the collection and also makes it possible to verify if the collection is genetically well represented. This study has as its objective to demonstrate the utilization of electrophoretic analysis for identifying clones of 14 breeding stocks of West Indian Cherry from the peroxidase and esterase isoenzymes. The results showed that the 14 clones of the breeding stocks of West Indian Cherry show activities typical of both isoenzymatic systems, and that these permit differentiating these clones and distinguishing between them and, with this, establishing the efficiency of these systems in aiding projects of vegetal genetic improvernent.